Lussazioni acromion-claveari - Spinelli, M.S.; Cugnetto, M.; Papalia, M.; Sessa, V. (Lo Scalpello - Journal, 2018)
THE SURGICAL TREATMENT OF ACROMIO-CLAVICULAR DISLOCATIONThe acromio-clavicular dislocation account approximatively the 10% of the shoulder girdle injury. This lesion is morefrequent in male, young and active patients who practice contact sports. Minor grade of dislocations usually remainundiagnosed and this leads to an underestimation of this lesion. The most commonly used classification is theRockwood’s one that is based on grade of dislocation and ligaments disruption, is divided in 6 grades, from a lesssevere to a more severe grade.The authors discuss anatomo-pathologic and epidemiologic aspects of the AC dislocation with indication forconservative and surgical treatment.